Penerapan Etika Bisnis Islam Dalam kegiatan Entrepeunership (Study kasus AHASS Putra Merdeka 01499 Surabaya) - zustika, anisa fadilah; ubaidillah, naufal (Jurnal Ilmiah Ekonomi Islam, 2023)
This study aims to analyze the application of Islamic Business Ethics in the management of the workshop Ahass Putra Merdeka 01499 Surabaya. The study used a qualitative approach by conducting indept interviews. Further analyzed using descriptive analysis methods. The results of this study concluded that the management of ahass putra merdeka 01499 Surabaya workshop in accordance with the basic values of Islamic Business Ethics. The first is the value of Tawheed to carry out buying and selling activities without a usury system and to sell certain goods, namely motor spare parts and providing services and understanding all ownership belongs to Allah so that the workshop owner performs zakat every year as an obligation and performs shodaqoh every day to help fellow human beings , both intellectual values and responsibilities, the third value of worship workshop owner requires for a matter of 5 times for employees so as not to leave the obligations of a muslim and perform prayers before doing activities to seek the pleasure and blessings of Allah, the fourth value tazkiyah owner apply the principles of honesty, justice, openness, the fifth value ihsan kindness to others, and togetherness. The results of the study stated that the basic values in Islamic business ethics have been fully applied in the management of Ahaas Putra Mederka 01499 Surabaya workshop. To support these values, it is necessary to upgrade several things both technically and facilities.